2008
DOI: 10.1097/ta.0b013e318184ee63
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Hypotension Redefined

Abstract: The definition of prehospital hypotension used for triage of injured patients to trauma centers should be redefined as PSBP < 110 mm Hg. The impact of this redefinition on trauma center resource utilization should be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 6 publications
4
42
0
2
Order By: Relevance
“…The mortality rate increases as blood pressure decreases below 120 mm Hg. This finding is similar to that of Eastridge et al 19 and Bruns et al 20 who found a SBP value of 110 mm Hg to be a better definition of hypotension in trauma patients. We demonstrate that this value is even higher in patients with TBI.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The mortality rate increases as blood pressure decreases below 120 mm Hg. This finding is similar to that of Eastridge et al 19 and Bruns et al 20 who found a SBP value of 110 mm Hg to be a better definition of hypotension in trauma patients. We demonstrate that this value is even higher in patients with TBI.…”
Section: Discussionsupporting
confidence: 85%
“…It would have been interesting to explore the relationship of emergency medical service first reported blood pressure values with mortality. Even though Bruns et al 20 demonstrate that emergency medical service and ED blood pressure values are highly correlated, this remains a limitation to our analysis.…”
Section: Discussionmentioning
confidence: 68%
“…Our research group has previously reported a similar continuous relationship between lower SBP values and mortality to that observed for TBI. [11] However, consistent with other recent studies, [43,44] the cut-off for increasing mortality was evident at a slightly lower level of 110mmHg. This may reflect the importance of even mild hypotension in increasing secondary brain injury.…”
Section: Sensitivity Analysessupporting
confidence: 89%
“…We chose to use a higher threshold (100 mmHg) of hypotension than the traditional 90 mmHg. This decision was based on increasing evidence advocating for a redefinition of arterial hypotension [8][9][10][11], which we also have underlined in a recent study within our research unit [12]. The primary date of contact defined the index date.…”
Section: Participantsmentioning
confidence: 99%